Discrimination Under Political or Other Opinions in Pre-contractual Labor Relationship (Journal of Legal Studies, 2024)
The legislative changes implemented in the Labor Code of Georgia fundamentally changed the regulations governing the prohibition of discrimination. In order to bring them closer to the law of the European Union, a number of important issues were identified that require scientific processing and comparative legal research. One of the current and problematic types of discrimination in Georgian reality is not hiring a person and/or dismissing him/her due to political or other opinions. Case law regarding these topics practically does not exist. The present article deals with the existing regulation related to discrimination due to political or other opinions in pre-contractual relationships. The present paper examines whether Georgian legislation complies with acts of ILO and European law.